2019
DOI: 10.24275/rmiq/ia650
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Adsorption Kinetics of Chromium (Vi) Using Waste Biomaterials

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The adsorption intensity, given by the Freundlich parameter (n) is high compared to other works using adsorbent materials of plant origin for Cr (VI) [24,26]. The Freundlich parameter (n) confirmed that the process can be classified as favorable for adsorption [10,21].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The adsorption intensity, given by the Freundlich parameter (n) is high compared to other works using adsorbent materials of plant origin for Cr (VI) [24,26]. The Freundlich parameter (n) confirmed that the process can be classified as favorable for adsorption [10,21].…”
Section: Discussionmentioning
confidence: 56%
“…Several methods have been reported for the removal of this metal due to the high resistance to degradation and biomagnification, such as: precipitation, oxidation, reduction, ionic exchange filtration, electrochemistry treatment, membrane technology, neutralization, electrocoagulation, inverse osmosis, catalytic oxidation, bioremediation, electrokinetic and evaporation [8][9][10]. However, implementation of these technologies implies high consumption of energy, operational costs, chemical additives, sludge accumulation and low efficiency at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active sites of absorption are occupied first by strong bonds, and this force decreases as they are occupied by the ions [54], [55]. The value of Freundlich's constant n (Table 4), is not in the range 1-10 which indicates that the chemical bonds formed between the ions and adsorbent are weak [54], [56], [57]. From equilibrium data to the Dubinin-Radushkevich model, a good fit was found for the Ni (II) and Pb (II) isotherm, with an R 2 higher than 0.98 in both cases and a qmax close to the experimental one.…”
Section: Adsorption Equilibriummentioning
confidence: 99%
“…On the other hand, the Colombian regulation about the punctual discharge to bodies of marine water establishes that the Cr (VI) discharge concentrations must be between 0.2-0.5 ppm, under Resolution 0883 of May 2018 [8]. However, concentrations of this metal could reach up to 450 ppm, for industrial effluents [9,10]. Among the various physicochemical processes, adsorption is one of the most effective and easy to implement methods [11,12].…”
mentioning
confidence: 99%